FEATURES OF DIALOGIC SPEECH - Jurayeva, Dilorom Rakhmatillo qizi (Educational Research in Universal Sciences, 2023)
When speaking a language, a person not only communicates information but also thinks and becomes aware of the hidden aspects of the natural world. Speech is the actual form of communication; language is merely a means of that. The language is not part of history, but the speech has historical characteristics. Language is a social phenomenon, while speaking is a mental phenomenon. The manner in which the speaker and the listener participate in communication are not necessarily the same. As a result, dialogic and monologic speech types develop. At the same time dialogic speech has several types. This paper presents information about dialogic speech.